2022
DOI: 10.26887/bcdk.v5i1.2493
|View full text |Cite
|
Sign up to set email alerts
|

Dramaturgi Bakaua dalam Masyarakat Minangkabau: Studi atas Ritual Tolak Bala Dengan Perspektif Victor Turner

Abstract: This article discusses the Bakaua ritual in the Minangkabau community, which is held in several places in the Sijunjung area. The Bakaua ritual is a ritual of expressing gratitude, as well as a ritual of rejecting reinforcements. Using a qualitative approach, the aim of this research is to find the structure as well as the anti-structure of the Bakaua ritual, in order to find out its symbolic meaning. The ritual structure is understood as a dramaturgy, by viewing ritual as a form of social drama. Research data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
4
0
6
Order By: Relevance
“…Menurut Harymawan (1993), dramaturgi adalah suatu disiplin ilmu yang mempelajari hukum dan konvensi drama. Sedangkan menurut Mary Luckhurst (dalam Pramayoza, 2013), pengertian dramaturgi berkaitan dengan: "Struktur internal dari sebuah teks lakon yang berkaitan dengan susunan elemenelemen formal lakon, meliputi plot, konstruksi narasi, karakter, kerangka waktu, dan aksi panggung…" Berdasarkan pandangan di atas, maka penelitian ini menggunakan teori struktur dan tekstur yang digagas George R. Kernodle (dalam Yudiaryani, 2002). Menurutnya, suatu proses penciptaan teater dapat diuraikan menjadi dua tahapan, dimulai dari struktur hingga menjadi tekstur.…”
Section: Kesenianunclassified
“…Menurut Harymawan (1993), dramaturgi adalah suatu disiplin ilmu yang mempelajari hukum dan konvensi drama. Sedangkan menurut Mary Luckhurst (dalam Pramayoza, 2013), pengertian dramaturgi berkaitan dengan: "Struktur internal dari sebuah teks lakon yang berkaitan dengan susunan elemenelemen formal lakon, meliputi plot, konstruksi narasi, karakter, kerangka waktu, dan aksi panggung…" Berdasarkan pandangan di atas, maka penelitian ini menggunakan teori struktur dan tekstur yang digagas George R. Kernodle (dalam Yudiaryani, 2002). Menurutnya, suatu proses penciptaan teater dapat diuraikan menjadi dua tahapan, dimulai dari struktur hingga menjadi tekstur.…”
Section: Kesenianunclassified
“…The study is carried out on a type of dramatic performance which is often not identified as theater, which lives in a particular area or ethnic community. Studies using this emic approach, for example, were carried out on ludruk in the Madurese community, lenong in the Betawi community, randai and sandiwara in the Minangkabau community, reyog in the Ponorogo community, drama gong in the Balinese community (Bouvier, 2002;Kleden-Probonegoro, 1996Pauka, 2002;Pramayoza, 2013Pramayoza, , 2016Simatupang, 2019;Yuliadi, 2005).…”
Section: Anthropological Approach: Cultural Performances Local Aesthe...mentioning
confidence: 99%
“…The result is an understanding of the life and development of ethnic aesthetics, namely the concept of beauty that only applies to one ethnicity, which cannot be generalized and equated arbitrarily with other ethnicities. What is seen as le'bur (fun) by the Madurese ethnic community (Bouvier, 2002), is not the same as ndadi (to be) for the people of Ponorogo (Simatupang, 2019), or taraso (feels) for the Minangkabau people (Pramayoza, 2013). However, these three are the highest aesthetic measurements used by each ethnic group in appreciating a dramatic performance of their own.…”
Section: Anthropological Approach: Cultural Performances Local Aesthe...mentioning
confidence: 99%
“…The emergence of an action to create a social phenomenon, good positive or negative towards consumers is the initial idea is born from individuals and then leads to community groups, as follows as a social action. The social action that Weber means is in the form of action is clearly directed towards another person, namely an action that thinks about or shown to other people which may occur due to the influence of certain situations, or also as an act of intentionally repeating the influence of certain situations similar, and passive consent in certain situations that have the effect of panic society in masse [26]- [28].…”
Section: The Covid-19 Phenomenon In Social Action Theorymentioning
confidence: 99%